Introduction to physics in modern medicine - Kane, Suzanne Amador (Boca Raton: CRC Press, 2009)
From x-rays to lasers to magnetic resonance imaging, developments in basic physics research have been transformed into medical technologies for imaging, surgery and therapy at an ever accelerating pace. Physics has joined with genetics and molecular biology to define much of what is modern in modern medicine. Covering a wide range of applications, Introduction to Physics in Modern Medicine, Second Edition builds on the bestselling original. Based on a course taught by the author, the book provides medical personnel and students with an exploration of the physics-related applications found in state-of-the-art medical centers. Requiring no previous acquaintance with physics, biology, or chemistry and keeping mathematics to a minimum, the application-dedicated chapters adhere to simple and self-contained qualitative explanations that make use of examples and illustrations. With an enhanced emphasis on digital imaging and computers in medicine, the text gives readers a fundamental understanding of the practical application of each concept and the basic science behind it. This book provides medical students with an excellent introduction to how physics is applied in medicine, while also providing students in physics with an introduction to medical physics. Each chapter includes worked examples and a complete list of problems and questions. That so much of the technology discussed in this book was the stuff of dreams just a few years ago, makes this book as fascinating as it is practical, both for those in medicine as well as those in physics who might one day discover that the project they are working on is basis for the next great medical application. This edition: Covers hybrid scanners for cancer imaging and the interplay of molecular medicine with imaging technologies such as MRI, CT and PET Looks at camera pills that can film from the inside upon swallowing and advances in robotic surgery devices Explores Intensity-Modulated Radiation Therapy, proton therapy, and other new forms of cancer treatment Reflects on the use of imaging technologies in developing countries
Includes bibliographical references.; Index 405-422p.
Keywords: Medical physics; Physice